Reporting quality evaluation of the stroke clinical practice guidelines: a systematic review - Shuya Lu (Systematic Reviews, 2021)
Abstract Objectives To analyze the effectiveness and quality of stroke clinical practice guidelines (CPGs) published in recent years in order to guide future guideline developers to develop better guidelines. Participants No patient involved Method PubMed, China Biology Medicine (CBM), Wanfang, CNKI, and CPG-relevant websites were searched from January 2015 to December 2019 by two researchers independently. The RIGHT (Reporting Items for Practice Guidelines in Healthcare) checklist was used to assess the reporting quality in terms of domains and items. Then, a subgroup analysis of the results was performed. Primary and secondary outcome measures RIGHT checklist reporting rate Results A total of 66 CPGs were included. Twice as many CPGs were published internationally as were published in China. More than half were updated. Most CPGs are published in journals, developed by societies or associations, and were evidence-based grading. The average reporting rate for all included CPGs was 47.6%. Basic information got the highest (71.7% ± 19.7%) reporting rate, while review and quality assurance got the lowest (22.0% ± 24.6%). Then, a cluster analysis between countries, publishing channels, and institutions was performed. There were no statistically significant differences in the reporting quality on the CPGs between publishing countries (China vs. international), publishing channels (journals vs. websites), and institutions (associations vs. non-associations). Conclusions Current stroke CPGs reports are of low quality. We recommend that guideline developers improve the quality of reporting of key information and improve the management of conflicts of interest. We recommend that guideline developers consider the RIGHT checklist as an important tool for guideline development. Trial registration https://doi.org/10.17605/OSF.IO/PBWUX .